Estimation of electronic programme guide use behaviour based on the switching cost evaluation - Frank, Domagoj (Array, 2018)
In this article we define a new technology acceptance research model which considers the comparison of two technology solutions that an individual can use. The model estimates the usage of the observed solution based on the cost of switching from the reference solution (typically a standard or older solution) to the observed solution, considering the fact that the cost of switching is caused by a difference of facilitating conditions, habit and the intention to use between the reference and observed solutions. For evaluation purposes, we observed the costs of switching from teletext use to the use of the electronic programme guide (EPG on the subset of n = 82 respondents and interpreted 77.2% of the variance, which demonstrates the high quality of the model. Evaluation results indicate that the primary obstacle to switching from teletext to EPG usage arises from the individuals’ perception whether they have more or less of the necessary resources to use the EPG in comparison to the resources they have at their disposition in case of teletext use, and the second ranked switching cost is caused by a difference in habit.